The other Eurostars: lifestyle migration, class and race among vocationally trained Italians. Issue 1 (2nd January 2023) - Varriale, Simone
ABSTRACT: This article investigates the aspirations for adventure, cosmopolitanism and self-exploration among non-graduate EU migrants from working- and lower-middle-class backgrounds. Drawing on interviews with Italians who moved to England after the 2008 economic crisis, and focusing on participants with vocational school diplomas, the article explores participants' lifestyle imaginaries, how these contextualise participants' economic concerns, and how they are negotiated in classed, racialised and gendered migrations. The findings reveal that these 'other Eurostars' come from class fractions endowed with relative, but unequally distributed, economic security and lower institutionalised cultural capital. This has a significant bearing on their motivations and experiences of migration, but without reducing them to mere economic instrumentalism. Indeed, participants approach employment as a means of self-realisation and status distinction, following aspirations that the extant literature ascribes to graduate migrants. The article contributes to lifestyle migration and intra-EU migration studies by revealing the centrality of non-economic motivations among less privileged EU migrants and showing that individualisation, as a late-modern project, is central to their migrations, but that it takes classed, racialised and gendered forms.